First German guideline on diagnostics and therapy of clinically non-functioning pituitary tumors - Deutschbein, Timo; Jaursch-Hancke, Cornelia; Knappe, Ulrich J.; Saeger, Wolfgang; Flitsch, Jörg; Bojunga, Jörg; Buchfelder, Michael; Ditzen, Beate; Gerlach, Rüdiger; Gertzen, Elfriede; Honegger, Jürgen; Horstmann, Gerhard A.; et al. (Experimental and clinical endocrinology & diabetes, 2021)
Although non-functioning pituitary tumors are frequent, diagnostic and therapeutic concepts are not well standardized. We here present the first German multidisciplinary guideline on this topic. The single most important message is to manage the patients by a multidisciplinary team (consisting at least of an endocrinologist, a neurosurgeon, and a (neuro-) radiologist). The initial diagnostic work-up comprises a detailed characterization of both biochemical (focusing on hormonal excess or deficiency states) and morphological aspects (with magnetic resonance imaging of the sellar region). An ophthalmological examination is only needed in presence of symptoms or large tumors affecting the visual system. Asymptomatic, hormonally inactive tumors allow for a 'wait and scan' strategy. In contrast, surgical treatment by an experienced pituitary surgeon is standard of care in case of (impending) visual impairment. Therapeutic options for incompletely resected or recurrent tumors include re-operation, radiotherapy, and observation; the individual treatment plan should be developed multidisciplinary. Irrespective of the therapeutic approach applied, patients require long-term follow-up. Patient with larger pituitary tumors or former surgery/radiotherapy should be regularly counseled regarding potential symptoms of hormonal deficiency states.
Gesehen am 03.05.2021